Increased monocytes and their derived indicators are associated with clinical severity of acute heart failure following acute myocardial infarction - Xinlin Xiong; Minsheng An; Li Yuan; Xiaobin Long; Shen Huang (Frontiers in Cardiovascular Medicine)
ObjectiveMonocytes play a significant role in the pathophysiology of acute myocardial infarction (AMI). The relationship between monocytes, their derived indicators, and the severity of acute heart failure following AMI remains unclear. Therefore, this study aims to investigate the association of monocytes and their derived indicators with clinical severity of acute heart failure in the patients with AMI.MethodsIn total of 173 patients with AMI were enrolled in this retrospective study. The demographic data and relevant medical histories were obtained. Monocytes and lipid levels were measured. All patients were divided into two groups based on killip classification. Killip class III-IV was defined as acute severe heart failure, while killip class I-II was defined as acute non-severe heart failure.ResultsMonocyte count, monocyte-to-white blood cell ratio, and monocyte-to-lymphocyte ratio were significantly higher in patients with acute severe heart failure compared to those with acute non-severe heart failure (P < 0.05). Multivariate logistic regression analysis showed that monocyte count, monocyte-to-white blood cell ratio, and monocyte-to-lymphocyte ratio were independently associated with acute severe heart failure (P < 0.05). Moreover, monocyte count, monocyte-to-white blood cell ratio, and monocyte-to-lymphocyte ratio were linked to NT-proBNP concentrations (P < 0.05). Receiver-operating characteristic curve analysis showed that monocyte count, monocyte-to-white blood cell ratio, and monocyte-to-lymphocyte ratio could identify acute severe heart failure in patients following AMI to some extent (P < 0.05).ConclusionThe elevation of monocyte count, monocyte-to-white blood cell ratio, and monocyte-to-lymphocyte ratio correlated with clinical severity of acute heart failure following AMI, and offered potential discriminating value for cardiogenic pulmonary edema and shock following AMI.